An Increased Burden of Highly Active Retrotransposition Competent L1s Is Associated with Parkinson’s Disease Risk and Progression in the PPMI Cohort - Pfaff, Abigail L.; Bubb, Vivien J.; Quinn, John P.; Koks, Sulev (International journal of molecular sciences, 2020)
Long interspersed element-1 (LINE-1/L1s) contributes 17% of the human genome with more than 1 million elements present; however, fewer than 100 of these have evidence for being retrotransposition competent (RC). In addition to those RC-L1s present in the reference genome, there are a small number of known non-reference L1 insertions that are also retrotransposition competent. L1 activity, whether through the potentially detrimental effects of their mRNA or protein expression or somatic retrotransposition events, has been linked to several neurological conditions. The polymorphic nature of both reference and non-reference RC-L1s in terms of their presence or absence will result in individuals harboring a different combination of these elements and it is currently unknown if this type of germline variation contributes to the risk of neurological disease. Here, we utilized whole-genome sequencing data from 178 healthy controls and 372 Parkinson’s disease (PD) subjects from the Parkinson’s Progression Markers Initiative (PPMI) to investigate the role of RC-L1s in PD. In the PPMI cohort, we identified 22 reference and 50 non-reference polymorphic RC-L1 loci. Focusing on 16 highly active RC-L1 loci, an increased burden of these elements (≥9) was associated with PD (OR 1.25, 95% CI 1.03–1.51, p = 0.02). In addition, we identified significant associations of progression markers of PD and the burden of highly active RC-L1s. This study has identified a novel type of genetic element associated with PD risk and disease progression.